Identification and Evaluation of Suitable Reference Genes for RT-qPCR Analysis in Hippodamia variegata (Coleoptera: Coccinellidae) Under Different Biotic and Abiotic Conditions - Xie, Jiaoxin; Liu, Tinghui; Khashaveh, Adel; Yi, Chaoqun; Liu, Xiaoxu; Zhang, Yongjun (Frontiers in Physiology, 2021)
Reverse transcriptase-quantitative polymerase chain reaction (RT-qPCR) is an accurate and convenient technique for quantifying expression levels of the target genes. Selection of the appropriate reference gene is of the vital importance for RT-qPCR analysis. Hippodamia variegata is one of the most important predatory natural enemies of aphids. Recently, transcriptome and genome sequencings of H. variegata facilitate the gene functional studies. However, there has been rare investigation on the detection of stably expressed reference genes in H. variegata. In the current study, by using five analytical tools (Delta Ct, geNorm, NormFinder, BestKeeper, RefFinder), eight candidate reference genes, Actin, EF1α, RPL7, RPL18, RPS23, Tubulin-α, Tubulin-β and TufA were evaluated under four experimental conditions including developmental stages, tissues, temperatures and diets. As a result, specific set of reference genes were recommended for each experimental condition. These findings will help to improve the accuracy and reliability of RT-qPCR data, and lay a foundation for further exploration on the gene function of H. variegata.